Beitrag zur Mikromaterialbearbeitung mit Excimerlasern - Systemkomponenten und Verfahrensoptimierungen - Rebhan, Thomas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1996)
The aim of the thesis is to increase the ablation rate of excimer laser material processing and thereby to promote the industrial applications. This should be realized by fundamental technology experiments and process optimization. For the first time a diffractive optical element (phase element) was used for XeCl excimer laser processing. The ablation rate increases by a factor of 3 to 4 for the used ring shaped focus in comparison to the conventional mask projection technique. The ablation rate of Al2O3-processing increases through the modification of the physical boundary conditions. If Al2O3 is processed in water the ablation rate is increased by an order of magnitude because water vaporizes explosively based on superheating. The application potential of excimer laser radiation in industry is improved because of the increase in efficiency (higher ablation rate, reduced optical losses